Investigation of Earthquake Behavior of the Church of St. Sergius and Bacchus in Istanbul/Turkey - Kocak, A.; Koksal, T. (TRANS TECH PUBLICATIONS LTD, 2010)
In this study The Church of St. Sergius and Bacchus was modeled by Finite Element Method and was put through various tests to determine its structural system, earthquake behavior and structural performance. The geometry of the structure, its material resistance and ground conditions isn't enough to model a historical structure. Additionally, you need to calculate the dynamic characteristics of the structure with an experimental approach to come up with a more realistic and reliable model of the structure. Therefore, a measured drawing of the structure was acquired after detailed studies, material testing were made both at summer and winter to examine the seasonal changes and soil conditions were determined by bore holes and exploratory wells dug around the structure. On the other hand, vibration tests were made at The Church of St. Sergius and Bacchus to analyze the structural characteristics and earthquake behavior of the building. Structural modeling of the building, modeled by the Finite Element Method, was outlined by determining its free vibration analysis in compliance with experimental periods. Vertical and earthquake loads of the structure were determined by this model. Keywords: Finite element method, earthquake behavior, church
Keywords: Construction & Building Technology; Engineering; Materials Science